Assessing the environmental impact of industrial pollution using the complex intuitionistic fuzzy ELECTREE method: a case study of pollution control measures - Ashraf, Shahzaib; Ali, Mubashar; Sohail, Muhammad; Eldin, Sayed M. (Frontiers in Environmental Science, 2023)
Environmental pollution has become a major issue in today's world and controlling it is crucial for the sustainable development of our planet. Industries play a significant role in environmental pollution and their impact must be controlled and minimized. In this paper, we present a novel approach, Complex Intuitionistic Fuzzy ELECTREE method (CIF ELECTREE), for environmental impact assessment of industries. The method combines the principles of Complex Intuitionistic Fuzzy Sets and ELECTREE method to provide a comprehensive and reliable assessment of the environmental impact of industries. The proposed method has been applied to real-world data and the results obtained demonstrate the effectiveness of the CIF ELECTREE method in controlling and reducing the environmental impact of industries. The results show that the CIF ELECTREE method can provide a more accurate assessment of the environmental impact of industries compared to traditional methods. This study contributes to the existing literature by introducing a novel approach for environmental impact assessment and highlights the importance of considering both the uncertainty and vagueness in real-world data for reliable decision making.